STRATEGI BERSAING PADA GELATIK RESIDENCE PALU - DJUMA, TANWIR (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
PT. Regional Trypillian is a company that is engaged in the development of new houses to prosper the society, especially by providing residence and develop its role in economic development in marketing the residential products and utilization of manpower. The establishment of the company initiated by Mr. Sofyan Hudri since February 15, 2014, starting from an attempt to manage, market, and produce home with investors/landowners. Wren's housing residence consists of 2 types: type 50 and type 90. The purpose of this study is to determine competition faced by Wren Residence in Palu and to examine alternative strategies that can be used by Wren Residence. Data analysis technique used is the SWOT analysis (Strength, Weakness, Opportunity, Threat). Based on the results of SWOT analysis in the form of matrix diagram and IE table, it finds that competitive strategies of Wren Residence is focused on aggressive strategy (growth-oriented strategy) that is suitable with the existing opportunities.